Aggressive CD5-Positive Primary Bone Marrow Diffuse Large B-Cell Lymphoma with Leukemic Presentation - Evans, Mark G.; Rezk, Sherif A.; Pinter-Brown, Lauren C.; Zhao, Xiaohui (Case Reports in Hematology, 2021)
Primary bone marrow diffuse large B-cell lymphoma is an exceedingly rare form of non-Hodgkin lymphoma. It may demonstrate a leukemic presentation, and a proportion of cases have CD5 expression. The prognostic implications of this CD5-positivity remain unknown. Here, we present a 78-year-old man who presented with circulating peripheral blood lymphoma cells and a hypercellular marrow involved by diffuse large B-cell lymphoma, germinal center B-cell subtype. The patient responded favorably to six cycles of etoposide, prednisone, vincristine, cyclophosphamide, doxorubicin, and rituximab (EPOCH-R) and intrathecal methotrexate. He unfortunately relapsed in several enlarged inguinal lymph nodes and succumbed to the lymphoma approximately one year after diagnosis, demonstrating the particularly aggressive clinical course of his disease.